Optimalisasi Citra Rekonstruksi Multiplanar Pada Ct Wrist Joint Dengan Perubahan Slice Thickness Dan Reconstruction Interval - Bagus Dwi Handoko; Jeffri Ardiyanto; Panji Wibowo Nurcahyo (Jurnal Riset Kesehatan, 2013)
The purpose of this study was to determain the value of slice thickness and reconstruction interval in which are able to produce an optimal image.Type of research is an experimental research with observational approach. Data retrieval is done by scanning with Scan 64 Slice MSCT in the wrist joint. Variations combination of slice thickness and interval Reconstruction by 9 (nine) times the variation of slice thickness between 0,5 mm, 1,0 mm, 1,5 mm and Reconstruction interval between 0,5, 1,0, 1,5.The results showed that to obtain optimal visualization of soft tissue and bone on MSCT scan examination Wrist Joint variation of slice thickness 0,5 mm and 1.5 Reconstruction interval can be selected. these variations produce optimal image quality with lower noise,